2019
DOI: 10.3390/ijms20102516
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid System in Hepatic Glucose Metabolism, Fatty Liver Disease, and Cirrhosis

Abstract: There is growing evidence that glucose metabolism in the liver is in part under the control of the endocannabinoid system (ECS) which is also supported by its presence in this organ. The ECS consists of its cannabinoid receptors (CBRs) and enzymes that are responsible for endocannabinoid production and metabolism. ECS is known to be differentially influenced by the hepatic glucose metabolism and insulin resistance, e.g., cannabinoid receptor type 1(CB1) antagonist can improve the glucose tolerance and insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 200 publications
(269 reference statements)
3
55
2
4
Order By: Relevance
“…ECS partially controls hepatic glucose and lipid metabolism as well as influences fibrogenesis and inflammation. Thus, ECS members, especially CB1 and GPR119, are promising targets in the treatment of liver diseases [241]. While CB1 promotes fibrogenesis, activation of CB2 results in antifibrogenic responses [241].…”
Section: Hepatic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…ECS partially controls hepatic glucose and lipid metabolism as well as influences fibrogenesis and inflammation. Thus, ECS members, especially CB1 and GPR119, are promising targets in the treatment of liver diseases [241]. While CB1 promotes fibrogenesis, activation of CB2 results in antifibrogenic responses [241].…”
Section: Hepatic Diseasesmentioning
confidence: 99%
“…Thus, ECS members, especially CB1 and GPR119, are promising targets in the treatment of liver diseases [241]. While CB1 promotes fibrogenesis, activation of CB2 results in antifibrogenic responses [241]. CB1 inhibition with rimonabant (10 mg/kg/day) in the mice model of nonalcoholic fatty liver disease (NAFLD) improved adipokine profile, decreased glucose plasma concentration, and reduced inflammation in adipose tissues and liver [242] and in the rat model of nonalcoholic steatohepatitis (NASH) inhibited hepatic fat infiltration, inflammation, fibrogenesis, and cellular death [243].…”
Section: Hepatic Diseasesmentioning
confidence: 99%
“…This system comprises endogenous cannabinoids (endocannabinoids, EC), their receptors (CB), and the enzymes responsible for their synthesis and degradation. EC have a multifaceted role: in physiological conditions as psychoactive, analgesic, antiemetic, anti-inflammatory, vasorelaxant, orexigenic [19,20,21,22] and in a myriad of pathological states such as neurodegenerative disorders [23,24,25], myocardial infarction [25], liver fibrosis [26], and cancer [27,28]. Therefore, pharmacologic intervention of the EC system is a promising strategy for the management of many diseases.…”
Section: Overview Of the Endogenous Cannabinoid Systemmentioning
confidence: 99%
“…EC are a class of arachidonic acid (AA) derivatives that interact with CB and were originally described as targets of Δ9-Tetrahydrocannabinol (THC), the main psychoactive constituent of Cannabis sativa [29]. EC share a common backbone structure resulting from their synthesis from membrane phospholipid precursors that contain AA and are conjugated either with ethanolamine or glycerol [22,26,30]. They are synthetized on demand, often in response to increased intracellular calcium concentrations [31].…”
Section: Overview Of the Endogenous Cannabinoid Systemmentioning
confidence: 99%
“…A separate study by Dr. Kunos’s lab showed that activation of CB1 increased glycogen phosphorylase activity by 70%, suggesting that enhanced glycogenolysis is the primary source of the increased HGP [ 53 ]. CB1 also inhibited insulin signaling in hepatocytes by activating the Bip/PERK/eIF2 α ER stress pathway [ 54 , 55 ]. Furthermore, another study showed that peripheral CB1 blockade in obese mice improved glycemic in control mice via the hepatic Sirt1/mTORC2/Akt pathway and increased fatty acid oxidation via LKB1/AMPK signaling [ 56 ].…”
Section: Role Of Gi-coupled Gpcrs In Liver Metabolismmentioning
confidence: 99%